Development of a Mobile-Healthcare Application for Safety and Prevention in Emergency Assistance at Marathon Events: A Case Study in CMU Marathon - Sirasakamol, Orasa; Ariya, Pakinee; Nadee, Wanvimol; Puritat, Kitti (International Journal of Online and Biomedical Engineering (iJOE), 2022)
The majority of marathon deaths are caused by sudden cardia arrest which occurs in approximately 1 in 100,000 runners around the world. In such cases, sudden resuscitation of first aid, including an early use of automated external defibrillator (AED) on runners by medical staff is immediately necessary. However, in some cases patient information of the runner is required to support the clinical decision-making of the medical staff, including the admission to hospital with certain symptoms. To make marathon events safer, we developed a mobile-healthcare emergency assistance application for safety and prevention in marathon events. Our project covers three phases: registration, data analytics and running phases. In the registration phase, we designed and developed a form containing the runner’s electronic personal health record filled in during the registration of the runner at the event. For the analytics and running phases, we analyze the data from the registration phase in order to prepare the capacity of resource and medical staff necessary to prevent and treat injuries and accidents including a sufficient number of AED devices. Finally, for the running phase, we developed a mobile application Medic and Track based on the qr code scanning in BIB for patient information that allows to locate the runner’s emergency aid point and bring the patient to that rescue point or hospital. We also tested the application on a large number of runners participating in the CMU marathon 2020 with 9721 runners. The results of this study suggest that the purpose of our application can be generally accepted for the medical staff, and it also proved to be a suitable technology to prevent serious accidents in future marathon events.